Development of a framework to promote rural health workforce capability through digital solutions: A qualitative study of user perspectives. (April 2022) - Ramsden, Robyn; Pit, Sabrina; Colbran, Richard; Payne, Kristy; Tan, Aaron JH; Edwards, Michael
A high-quality, sustained, health workforce contributes to a healthy population. However, a global reality is that rural health services, and the workforces that provide those services, are under unprecedented pressure. It is posited that improving a rural health practitioners' capability could help to retain them working rurally for longer. Capability refers to skills and experience and the extent to which individuals can adapt to change, generate new knowledge and continue to improve their performance. With rapidly increasing access to, and use of, digital technology worldwide, there are new opportunities to build capability and leverage personal and professional support for those who are working rurally. In 2021, semi-structured interviews were conducted in rural Australia with thirteen General Practitioners and allied health professionals. Thematic analysis was adopted to analyse the data and map it to the Health Information Technology Acceptance Model. Whilst it could be assumed that low technology literacy would act as a barrier to the use of digital tools, the study demonstrated that this was not a significant impediment to participants' willingness to adopt digital tools when social and professional networks weren't available face to face to address their capability challenges. The findings provide insight into the concept of health workforce capability and important considerations when designing capability support. This includes key features of health apps or digital tools to support the capability of the rural health workforce. Understanding the factors that make up a health professionals' capability and the motivations or cues to act to build or maintain their capability may have a positive effect on their retention in a rural location.